Innføring av digitale sentralbankpenger - nødvendige lovendringer - Helge Syrstad (Norges Bank, 2023)
Norges Bank has been running a central bank digital currency project since 2016. The project is now in its fourth phase, and as part of this phase an overview will be provided of required legislative amendments linked to the introduction of CBDC. For an overview of Norges Bank's CBDC project, please see the web page on central bank digital currency (https://www.norges-bank.no/en/topics/financial-stability/central-bank-digital-currency/). This memo assesses the legislative amendments that are expected to be required in order to introduce CBDC.
hdl:11250/3050873
Keywords: 330; Virtuelle Währung; Zentralbank; Währungsrecht; Norwegen